Contemporary Expressions of Personal Law: Co-Existence or Conflict with the Territorial Law? - Izdebski, Hubert (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The paper concerns the present role played in law-in-the-books and law in action as well by a very traditional law type, namely that of personal law. In spite of the dominating role that the other type, i.e. territorial law, has played in Western law for more than a thousand years, there are numerous contemporary expressions of the existence and application of personal laws. In particular, this is the case of the vivacity of traditional personal laws characteristic of non-Western legal traditions (above all shari’a), including attempts at their application in the Western environment. There are also various other examples of the recognition, at least in the practice, of personal laws in the Western law jurisdictions, which is indicated with the example of Polish law.